Effects of paylean (ractopamine⋅HCl) on finishing pig growth and variation - Barker, M.R.; Groesbeck, C.N.; Hanni, S.M.; Hastad, C.W.; Keegan, T.P.; Lawrence, K.R.; Young, M.G.; Goodband, Robert D.; Tokach, Michael D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 336 pigs were used in a 21-day trial to determine the effect of Paylean (9.0 g/ton Ractopamine·HCl) on finishing pig growth and variation. Pigs were allotted based on weight so that all pens had the same initial weight and degree of variation within the pen. Pigs fed Paylean had greater ADG and better feed efficiency than control-fed pigs (P<0.05). However, no differences in pen coefficient of variation were observed (P>0.70). The results suggest that adding Paylean to the diet improves finishing pig growth performance but does not affect weight variation within the pen.
Keywords: Swine; Ractopamine; Paylean; Variation